Insight into Oxygen Transport in Proton Exchange Membrane Water Electrolyzers by In Situ X‐Ray Characterization - Ping'an Li; Zihan Zhou; Diankai Qiu; Linfa Peng (Advanced Science)
Abstract The proton exchange membrane water electrolyzer (PEMWE) is one of the most promising electrochemical energy conversion devices for hydrogen production, while still limited by performance bottlenecks at high current densities, due to the lack of mass transfer insights. To investigate the mechanisms of oxygen transport inside the PEMWE at high current density and its relation to electrolytic performance. Operational in situ x‐ray imaging is utilized to simultaneously characterize the bubble behavior and voltage response in a novel designed visual mini‐cell, and it is identified that oxygen evolution and transport in the PEMWE follow the process of bubble nucleation, growth, and detachment. Based on the results of mini‐cells with three porous transport layers (PTLs) up to 9 A cm−2 operation, it revealed that critical current densities exist for both carbon‐based and titanium‐based PTLs. Once exceeding the critical current density, the cell voltage can no longer be stabilized and the cell exhibits a significant oxygen overpotential. To illustrate this, the concept of interfacial separation zone (ISZ) is first proposed, which is an effective pathway for bubble growth and separation and the pattern of the ISZ exhibits specific regimes with the critical current density. Ultimately, a new approach for better understanding the mechanisms of oxygen transport is revealed.